TINGKAT KEBERHASILAN INSEMINASI BUATAN (IB) PADA SAPI LIMOSIN DI KABUPATEN LAMPUNG TENGAH: Success Rate Of Artificial Insemination (AI) In Limosin Cattle In Central Lampung District - Herdiansah, Riko; Sugesti, Madiyan; Romadhon, Rifki (Wahana Peternakan, 2024)
Artificial insemination is one of the biotechnologies in livestock reproduction that allows the mating process of female livestock to be carried out without the presence of a male. AI involves a series of procedures that are designed in a planned and programmed manner, with the aim of improving the genetic quality of livestock in the future. AI technology is a solution to accelerate the increase in the beef cattle population. The opportunity for beef cattle farming in Seputih District, Surabaya, Central Lampung Regency has great potential to be developed because it can provide benefits for the community who raise livestock. From this, it is necessary to study the success rate of artificial insemination (AI) in Limousin cattle in Central Lampung Regency. This study was conducted in November 2023 in Srikaton Village (SK3), Seputih District, Surabaya, Central Lampung Regency. The variables observed included Respondent Characteristics, Service Per Conception (S/C), and Conception Rate (CR). From the results of the study, it can be concluded that Service per Conception (S/C) was recorded at 1.32. High S/C values ​​tend to cause longer birth intervals compared to livestock that have normal birth intervals of 12 months. In addition, the Conception Rate (CR) obtained in this study reached 75.3%, which is in accordance with the ideal standard (CR) of cattle ranging from 60-75%, where the higher the CR value, the better the fertility rate of the livestock. Keywords: IB Success, Service Per Conception (S/C), and Conception Rate (CR)